Spousal Influence on Physical Activity in Middle-Aged and Older Adults: The ARIC Study. Issue 5 (2nd September 2015) - Cobb, Laura K.; Godino, Job G.; Selvin, Elizabeth; Kucharska-Newton, Anna; Coresh, Josef; Koton, Silvia
Abstract : Low physical activity levels are a public health concern. Few studies have assessed the concordance of physical activity change among spouses. We studied this concordance during a 6-year period (baseline: 1987–1989; follow-up: 1993–1995) in 3, 261 spousal pairs from the US-based Atherosclerosis Risk in Communities (ARIC) Study. Linear regression was used to examine the association between change in individuals' sport/exercise and leisure physical activity indices (ranging from 1 (low) to 5 (high)) and change in his or her spouse's indices. The association between individual and spousal changes in meeting physical activity recommendations was assessed with logistic regression. Individual changes in the sport/exercise and leisure indices were positively associated with spousal changes. For every standard deviation increase in their wives' sport/exercise index, men's exercise index increased by 0.09 (95% confidence interval: 0.05, 0.12) standard deviation; for every standard deviation increase in their wives' leisure index, men's leisure index increased by 0.08 standard deviation. Results were similar for women. Individuals had higher odds of meeting physical activity recommendations if their spouse met recommendations at both visits or just follow-up. In conclusion, changes in an individual's physical activity are positively associated with changes in his or her spouse's physical activity. Physical activity promotion efforts should consider targeting couples.